PENGARUH RETURN ON ASSET, LONG TERM DEBT TO EQUITY RATIO, CURRENT RATIO, TOTAL ASSET TURNOVER, DAN SUKU BUNGA TERHADAP HARGA SAHAM PADA GRUP PERUSAHAAN MINYAK DAN GAS BUMI - ROSMIATI (AKADEMIKA, 2019)
This study aims to examine the effect of Profitability ratio represented by Return On Asset (ROA), Solvency ratio represented by Long Term Debt to Equity ratio, Liquidity ratio represented by Current ratio Activity ratio represented by Total Asset Turn Over, and Indonesian Interest Rates, which of variables those variables that have an influence on stock prices on Oil and Gas Companies Listed On Indonesia Stock Exchange Period 2010-2014. The type of research used in this study is quantitative research that is associative causal. The population in this study as Oil and Gas companies Listed On Indonesia Stock Exchange Period 2010-2014. used as a sample of 7 companies. The data used in this research is secondary data with panel data type which sourced from official website of Indonesia Stock Exchange. Data analysis technique used in this research is panel data regression analysis with statistical model test using partial test (t test), simultaneous test (F test), and coefficient of determination. The results simultaneous test (F test) show that the variable Return On Asset (ROA), Long Term Debt to Equity ratio, Current ratio, Total Asset Turn Over, and Indonesian Interest Rates are influential positively and significantly tostock prices. Result of partial test (t test) show Return on Asset are influential positively and significantly to stock prices. While Long Term Debt to Equity ratio, Current ratio, Total Asset Turn Over, and Indonesian Interest Rates does not have a positive and significant effectto stock prices at Oil and Gas companies listed in Indonesia Stock Exchange.